Creating the British Atlantic : essays on transplantation, adaptation, and continuity - Greene, Jack P. (Early American histories., 2013)
In these essays, the author explores the efforts to impose Old World institutions, identities, and values upon the New World societies being created during the colonization process. He shows how transplanted Old World components - political, legal, and social - were adapted to meet the demands of new, economically viable, expansive cultural hearths. The author argues that these transplantations and adaptations were of fundamental importance to the formation and evolution of the new American republic and the society it represented. -- Description from back cover of paperback.